COBIT, Control Tool in Business Management - Rivera León, Félix Armando (2019)
In line with new business needs and trends such as: “COSO (Committee of Sporisoring Organization of the treadway Commission Internal Control-Integrated Framework, 1992 in the US, Cadhuay in the United Kingdom, CoCo in Canada and King in South Africa, and the coexistence of control models at the information technology levels such as: Security Code of conduct of the DTT (Department of Industry and Commerce, United Kingdom) and the Security Handbook of Nist (National Institute of Standards and technology, USA).” Given the need that the aforementioned models do not provide a complete and usable control model in business management, the ISACF (Information Systems Audit an Control foudation) and ITGI (Governance Institute), develop COBIT to cover the pre-existing vacuum to achieve the aims planned in the organizations, with the development with the new point of view that the new information technologies plan. COBIT integrates and consolidates rules and regulations already indicated by the aforementioned institutions.